Competitive Specific Anchorage of Molecules onto Surfaces: Quantitative Control of Grafting Densities and Contamination by Free Anchors - Kirichuk, Oksana; Srimasorn, Sumitra; Zhang, Xiaoli; Roberts, Abigail R E; Coche-Guerente, Liliane; Kwok, Jessica C F; Bureau, Lionel; Débarre, Delphine; Richter, Ralf P (Langmuir, 2023)
The formation of surfaces decorated with biomacromolecules such as proteins, glycans, or nucleic acids with well-controlled orientations and densities is of critical importance for the design of in vitro models, e.g., synthetic cell membranes and interaction assays. To this effect, ligand molecules are often functionalized with an anchor that specifically binds to a surface with a high density of binding sites, providing control over the presentation of the molecules. Here, we present a method to robustly and quantitatively control the surface density of one or several types of anchor-bearing molecules by tuning the relative concentrations of target molecules and free anchors in the incubation solution. We provide a theoretical background that relates incubation concentrations to the final surface density of the molecules of interest and present effective guidelines toward optimizing incubation conditions for the quantitative control of surface densities. Focusing on the biotin anchor, a commonly used anchor for interaction studies, as a salient example, we experimentally demonstrate surface density control over a wide range of densities and target molecule sizes. Conversely, we show how the method can be adapted to quality control the purity of end-grafted biopolymers such as biotinylated glycosaminoglycans by quantifying the amount of residual free biotin reactant in the sample solution.
Keywords: biopolymery; buněčná membrána; Cell Membrane; biotin; Biopolymers; Biotin